The company constitution as a contract with emphasis on the outsider rule - Fredman, Michael Geoffrey (Centre for Law and Society, 2026)
The -concept of the company ·constitution as a-contract will be examined in three parts~. The -first part is devoted to the legal nature of the constitution. It will examine the role of the two sources of its nature and sanction, namely the contractual and the statutory. It wi1l also identify the parties to the constitution and accordingly the contracts to be found therein. -Then consideration will be given to the possibility in law of altering the company constitution by the unanimous consent of-all its members, without complying with the formalities ·tor such alteration as are prescribed by statute. In addition, attention will be given t6 the problem of rectifying mistakes in the constitution once it is registered. These topics serve, to cast light on the legal riature of the company constitution. The second part is concerned with aspects of the enforcement of rights arising from the contract embodied in the constitution. One such aspect ·is the proposition that continued membership of a company is a barrier to an action for. damages against that company. -Another aspect is the ultra vires doctrine under the common law in terms of which acts beyond~ the capacity and powers of a company are void. Since the ·memorandum and articles institute a contract; the members rights in relation to such an act wil1 be considered. The· important changes to this common law doctrine wrought by s36 of the Companies Act, 1973 will also receive~ detailed attention. Another aspect is the rule in Foss v Harbottle, which circumscribes the rights of a member to take action to enforce rights arising from the constitution, firstly in regard to a wrong done to the company, · and secondly, in matters of internal management, where the ·irregularity is capable of ratification by a simple majority. Consequential difficulties in the definition and the enforcement 6f the member's personal rights will also receive attention. The third part is devoted to another major topic to which special attention will be given, namely the outsider rule. It declares that rights purporting to be given by an article in a capacity other than that of a member, cannot be enforced against the company. Its· effect in limiting the scope of the contract ~embodied in the constitution, and, therefore, its role as an obstacle to the enforcement of contractual rights embodied in the constitution, will occupy the remaining chapters of this dissertation.